Activity-dependent regulation of synapse and dendritic spine morphology in developing barrel cortex requires phospholipase C-beta1 signalling. - Spires, T; Molnár, Z; Kind, P; Cordery, P; Upton, A; Blakemore, C; Hannan, A (2005)
The phospholipase C-beta1 (PLC-beta1) signalling pathway, activated via metabotropic glutamate receptors (mGluRs), is implicated in activity-dependent development of the cerebral cortex, as both PLC-beta1 and mGluR5 knockout mice exhibit disrupted barrel formation in somatosensory cortex. To characterize the effects of this signalling system on development of synaptic circuitry in barrel cortex, we have examined neuronal ultrastructure, synapse formation and dendritic spine morphology in PLC-beta1 knockout mice. Qualitative ultrastructure of neurons and synapse density in layers 2-4 of barrel cortex were unchanged in PLC-beta1 knockout mice during development [postnatal day (P) 5] and in mature cortex (P19-21). We found a decrease in the proportion of synapses with symmetric morphology at P5 that was gone by P19-21, indicating a transient imbalance in excitatory and inhibitory circuitry. We also investigated dendritic spines by back-labelling layer 5 pyramidal neurons with carbocyanine. We observed normal dendritic spine densities on apical dendrites as they passed through layer 4 of barrel cortex, but spine morphology was altered in PLC-beta1 knockout mice at P9. These observations indicate that the PLC-beta1 signalling pathway plays a role in the development of normal cortical circuitry. Interrupting this regulation leads to changes in synapse and dendritic spine morphology, possibly altering post-synaptic integration of signal.